PENINGKATAN PERILAKU PROSOSIAL ANAK MELALUI METODE BERMAIN PERAN MAKRO PADA USIA 4-5 TAHUN DI TAMAN KANAK-KANAK IMMANUEL PONTIANAK - Cristanti, Levina Faustine; Marmawi R, Marmawi R; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to determine the increase in prosocial behavior of children through the method of playing macro roles in children aged 4-5 years at the Immanuel Kindergarten in Pontianak. The research method used was classroom action research conducted in 2 cycles. Each cycle is done in 2 meetings. The data source of this study were children aged 4-5 years of the A4 group of 25 children and the data were observation sheets for teachers, children and documentation. Data processing uses a percentage calculation method. The conclusion of the results of the method of playing macro roles for children aged 4-5 years at the Immanuel Pontianak Kindergarten in Increasing the prosocial behavior of children increased in cycle 2 meeting 2 on the aspect of children being enthusiastic in playing games with friends reaching 96% with very good categories, children obey the rules (patiently waiting their turn) reaches 100% with very good categories, children respect others (working together) reaches 100% with very good categories and children show concern (helping) reaching 92% with very good categoriesKeywords: Children Aged 4-5 Years, Child Prosocial Behavior, Macro Role Playing Method